ANALISIS IMPLEMENTASI BPEL DAN MOBILE AGENT (AGLETS) STUDI KASUS APLIKASI INFORMASI KEGIATAN PARIWISATA DAN BIRO PERJALANAN - , Fadelis Sukya, Dr. Ahmad Ashari, M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Web services technologies is a common standard in building applications using XML standards. Development of web service application interface, it is not enough to provide completeness in the coordination of business processes. therefore, necessary approach to develop web services concurrently to establish the definition of process and service orchestration. This study will analysis of the implementation of BPEL and mobile agents (aglets) in a travel agency application. Travel agency model that produced a model that describes the interactions between web services applications involved and their relationship to control the interaction of central coordination. In the implementation of case studies that apply business process which is the provision of information on the tourism department of tourism district of Kediri, Malang, Yogyakarta and flight ticket booking transaction. Business Process Management System (BPMS) used to support the design, execution, and monitoring business processes. Test results showed that implementation using aglets at the travel agency has completed the process needs time performance is better when compared to using BPEL. analysis process using the processing time measurement processing statistical data and manually compare the processing time of each system. The resulting system is successfully implemented on the operating system is different.